MODAL SOSIAL PEDAGANG BUAH KIOS DI PASAR PAGI ARENGKA BARU KOTA PEKANBARU - Dian Suci Hasyyati; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at Pagi Arengka Baru Market, Mapoyan Damai District, East Sidomulyo Timur Pekanbaru with the following problems, namely (1) How are the elements of social capital developed by fruit stall traders ar Arengka Baru Market, Pekanbaru City (2) What are types of social capital for fruit traders in the Arengka Baru market in Pekanbaru City. The purpose of this study was to analyze the analysis data, know and describe how the elements of social capital in the fruit stall traders at the Arengka Baru market, and to analyze the data, and to find out the types of social capital developed by fruit stall traders in the Arengka Baru market, Pekanbaru City. This research uses destiptive qualitative research methods, The subjects in this study were taken usin purposive sampling technique, namely they are fruit kiosk traders who sell various types of fruit in Arengka Baru market Pekanbaru City. To collect research data using in-depth interview guide data, observation and documentation. The results of study found that the norms in fruit traders (negotiation systems, goods damage system, deliberation) were formed because of the agreed and upheld norms, asa well as the existence of values (kinship, brotherhood, honesty, and patience by each individual). Network (Bounding Social Capital, namely similarity in ethnicity, and similarity in fate). Bridging social capital: (towards new agents who offer cooperation and expand customers) is formed because there is a meeting poit of common values and norms and the existence of cooperation. This cooperation can be created with a common identity and reciprocal norms. Fruit traders’ trust id formed automatically along with the information of norms and networks. Keywords: Social Capital, Types of Social Capital, Kiosk Fruit Merchants